1999
DOI: 10.1074/jbc.274.29.20092
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity Spectrum, cDNA Cloning, and mRNA Expression of a Newly Isolated Member of the Cecropin Family from the Mosquito Vector Aedes aegypti

Abstract: An antimicrobial peptide belonging to the cecropin family was isolated from the hemolymph of bacteriachallenged adult Aedes aegypti. This new peptide, named cecropin A, was purified to homogeneity and fully characterized after cDNA cloning. The 34-residue A. aegypti cecropin A is different from the majority of reported insect cecropins in that it is devoid of a tryptophan residue and C-terminal amidation. The importance of these two structural features on the activity spectrum was investigated using a chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 43 publications
4
111
0
7
Order By: Relevance
“…However, the absence of cysteines and the distribution of hydrophobic and polar amino acids in the primary structure indicate that the peptide may adopt a ␣-helical structure like that of insect cecropins. This prompts a comparison between the biological properties of spinigerin and two representatives of the amphipathic ␣Ϫhelical antimicrobial peptides: Aedes aegypti cecropin (8) and PGLa from Xenopus laevis (26) (see Table II). Spinigerin showed activity against two of the six Gram-positive bacteria tested, namely M. luteus and B. megaterium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the absence of cysteines and the distribution of hydrophobic and polar amino acids in the primary structure indicate that the peptide may adopt a ␣-helical structure like that of insect cecropins. This prompts a comparison between the biological properties of spinigerin and two representatives of the amphipathic ␣Ϫhelical antimicrobial peptides: Aedes aegypti cecropin (8) and PGLa from Xenopus laevis (26) (see Table II). Spinigerin showed activity against two of the six Gram-positive bacteria tested, namely M. luteus and B. megaterium.…”
Section: Discussionmentioning
confidence: 99%
“…Cecropins, proline-rich, and glycine-rich peptides are essentially active against Gram-negative cells, but their activity spectrum sometimes includes Gram-positive bacteria as targets (6). Two recent reports have also indicated that cecropins can also exert antifungal properties (7,8). Among the open ended cysteine-rich peptides, insect defensins are the most widespread (9).…”
mentioning
confidence: 99%
“…aegypti mosquitoes. The protein was active against a broad spectrum of Gram-negative bacteria but less so against Gram-positive bacteria and fungi (Lowenberger et al, 1999a). The Anopheles genome encodes four defensin genes (DEFs), four cecropins (CECs), one attacin and one gambicin (GAM1) .…”
Section: Pathogen Elimination Antimicrobial Peptides (Amps)mentioning
confidence: 99%
“…These families include defensin and cecropin, which are the only classes of antimicrobial peptides so far reported in mosquitoes (10)(11)(12)(13)(14). Mosquitoes also contain genes encoding lysozyme (15)(16)(17).…”
Section: T He Mosquito Anopheles Gambiae Is the Major Vector Ofmentioning
confidence: 99%